2016
DOI: 10.1002/adfm.201601125
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Tuning of the Energetics in Singlet Fission Organic Solar Cells

Abstract: 6489wileyonlinelibrary.com conversion effi ciency (PCE) of a single junction solar cell is 41.9%-a signifi cant improvement over the so-called Shockley-Queisser limit of 32% for conventional devices. [ 6,7 ] The theoretical maximum PCE can be boosted even further if a long wavelength absorber is incorporated to take advantage of solar photons with energies between the singlet and triplet levels of the singlet fi ssion material. [ 1,3,8 ] Because of these exciting prospects, singlet fi ssion solar cells have at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…[9,24,25] In their aggregated states, donor or acceptor domains typically have lower ionization potentials and increased electron affinities than the nonaggregated phases owing to polarization and delocalization effects. [15,28] The presence of such structural heterogeneities at the proximity of D-A interfaces will thus invariably influence the V OC . [15,28] The presence of such structural heterogeneities at the proximity of D-A interfaces will thus invariably influence the V OC .…”
Section: In Organic Solar Cells (Oscs) the Energy Of The Charge-tranmentioning
confidence: 99%
“…[9,24,25] In their aggregated states, donor or acceptor domains typically have lower ionization potentials and increased electron affinities than the nonaggregated phases owing to polarization and delocalization effects. [15,28] The presence of such structural heterogeneities at the proximity of D-A interfaces will thus invariably influence the V OC . [15,28] The presence of such structural heterogeneities at the proximity of D-A interfaces will thus invariably influence the V OC .…”
Section: In Organic Solar Cells (Oscs) the Energy Of The Charge-tranmentioning
confidence: 99%
“…Moreover, the energy of the CT state correlates with the open-circuit voltage value in an organic solar cell. 3,4 Therefore, understanding the energetics and nature of CT states and correlating them with interfacial morphologies 5 are essential. Theoretical investigations on organic/organic interfaces have provided microscopic information regarding the energies and wave function properties of the CT states.…”
Section: Introductionmentioning
confidence: 99%
“…[19] But TAS literature has shown that intermolecular interactions that result upon solidification can alter singlet and triplet energy levels and ISC kinetics. [2,[25][26][27] To assess, we turn to the grazing-incidence X-ray diffraction (GIXD) pattern of as-deposited TBF films, which shows a broad amorphous halo centered about q = 0.5 Å -1 , indicating weak sub-nanometer nearest-neighbor correlations. [19,28] These nearest-neighbor interactions could indicate local TBF aggregation, which would result in low-order triplet excimers when TBF neat films are photoexcited.…”
Section: Steady-state Emissionmentioning
confidence: 99%
“…Figure 7 proposes a Jablonski diagram that is consistent with TBF neat films having broad, energetically-overlapping singlet-and triplet-excimer states in equilibrium via an energetically-diverse range of singlet states given band splitting. The singlet and triplet excimer bands in Figure 7 Figure S13) by sensitive EQE spectroscopy [2] reveal the CT states of TBF/C 60 and TBF/12Cl to have energies centered at 1.24 and 1.77 eV, respectively, with the CT band of TBF/12Cl only subtly visible due to the optical response of the neat constituents. The CT band of TBF/8Cl is expected to be ≄ 0.3 eV higher than that of the CT band of TBF/12Cl, and cannot be resolved from the bulk TBF/8Cl EQE response ( Figure S13c).…”
Section: Implications For Organic Photovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation